Newborn amygdala connectivity and early emerging fear. (June 2019) - Thomas, Elina; Buss, Claudia; Rasmussen, Jerod M.; Entringer, Sonja; Ramirez, Julian S.B.; Marr, Mollie; Rudolph, Marc D.; Gilmore, John H.; Styner, Martin; Wadhwa, Pathik D.; Fair, Damien A.; Graham, Alice M.
Highlights: Newborn Am-Ins connectivity predicts fear development from 6 to 24 months-of-age. Newborn Am-vMPFC connectivity predicts sadness development from 6 to 24 months-of-age. Distinct newborn amygdala connections support fear versus sadness development. Abstract: Connectivity between the amygdala, insula (Amygdala-aI) and ventral medial prefrontal cortex (Amygdala-vmPFC) have been implicated in individual variability in fear and vulnerability to psychiatric disorders. However, it is currently unknown to what extent connectivity between these regions in the newborn period is relevant for the development of fear and other aspects of negative emotionality (NE), such as sadness. Here, we investigate newborn Am-Ins and Am-vmPFC resting state functional connectivity in relation to developmental trajectories of fear and sadness over the first two years of life using data from the Infant Behavior Questionnaire Revised (IBQ-R) and Early Childhood Behavior Questionnaire (ECBQ) (N=62). Stronger newborn amygdala connectivity predicts higher fear and sadness at 6-months-of-age and less change from 6 to 24-months-of-age. Interestingly, Am-Ins connectivity was specifically relevant for fear and not sadness, while Am-vmPFC was associated only with sadness. Associations remained consistent after considering variation in maternal sensitivity and maternal postnatal depressive symptomology. Already by the time of birth, individual differences in amygdala connectivity are relevant for the expression of fear over the first two-years-of-life. Additionally, specificity is observed, such that connections relevant for fear development are distinct from those predicting sadness trajectories.